How Down is a Downbeat? Feeling Meter and Gravity in Music and Dance - Jonathan Still (Empirical Musicology Review, 2015)
The idea that metrical accent might be related to an embodied sense of "up" and "down" is implied by the terms "upbeat" and "downbeat," and is central to theories of meter as gravitational field, such as those evolved by Robert Hatten and Steve Larson. Yet as Hatten himself notes, upbeats and downbeats do not always map conveniently on to upward or downward movements in dance. Drawing on ethnographic research among trainee ballet teachers and recent theories of musical meter, this article discusses some practical and theoretical problems that arise when trying to teach about meter in the context of ballet training. It is suggested that empathic listening and perspective taking, rather than appeals to common embodied experiences of meter, may be key to developing better interdisciplinary understanding between musicians and dancers.